Concussion [videorecording (DVD)] - Landesman, Peter, 1965-; Smith, Will, 1968-; Baldwin, Alec, 1958-; Brooks, Albert, 1947-; Mbatha-Raw, Gugu, 1983- (Sony Pictures Home Entertainment, 2016)
A dramatic thriller based on the incredible true David vs. Goliath story of American immigrant Dr. Bennet Omalu, the brilliant forensic neuropathologist who made the first discovery of CTE, a football-related brain trauma, in a pro player and fought for the truth to be known. Omalu's emotional quest puts him at dangerous odds with one of the most powerful- and beloved- institutions in the world.